2018
DOI: 10.1038/s41598-018-33608-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Lithium Quantification in LiXNiyCowMnZO2 as Cathode for Rechargeable Batteries

Abstract: Time-of-flight secondary ion mass spectrometry (TOF-SIMS) using a focused ion-beam scanning electron microscope (FIB-SEM) is a promising and economical technique for lithium detection and quantification in battery materials because it overcomes the limitations with detecting low Li content by energy dispersive spectroscopy (EDS). In this work, an experimental calibration curve was produced, which to our best knowledge allowed for the first time, the quantification of lithium in standard nickel manganese cobalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…SIMS is a powerful surface‐sensitive technique that allows the imaging of all chemical compositions covering Li, with sub‐100‐nm lateral and nanometer depth spatial resolution. [ 123 ] To date, one of the most popular SIMS instruments is the time‐of‐flight SIMS (TOF‐SIMS). TOF spectrometer separates secondary ions based on their mass‐to‐charge ratio ( m / z ) formed by the primary‐ion bombardment.…”
Section: Multiscale Characterizations Of Nrlo Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…SIMS is a powerful surface‐sensitive technique that allows the imaging of all chemical compositions covering Li, with sub‐100‐nm lateral and nanometer depth spatial resolution. [ 123 ] To date, one of the most popular SIMS instruments is the time‐of‐flight SIMS (TOF‐SIMS). TOF spectrometer separates secondary ions based on their mass‐to‐charge ratio ( m / z ) formed by the primary‐ion bombardment.…”
Section: Multiscale Characterizations Of Nrlo Degradationmentioning
confidence: 99%
“…By correlating with FIB‐SEM, TOF‐SIMS offers unique imaging and analytic capabilities of bulk LIB samples. [ 123,125 ] The nanoscale elemental distributions of the charged and discharged Li 1− x Mn 0.54 Ni 0.13 Co 0.13 O (2− x ) particles were mapped by TOF‐SIMS. In this work, non‐uniform elemental distribution and “trapped” Li‐ion sites at the grain boundaries were revealed (Figure 9b).…”
Section: Multiscale Characterizations Of Nrlo Degradationmentioning
confidence: 99%
“…TOF-SIMS has been applied to cross sections of lithium-ion battery electrodes to map elemental distributions of lithium and other metals within particles with resolutions of 10s of nanometers (Figure 2c). [39,40] The fields of view for these techniques are also variable depending on the time and data-storage capabilities available, but are generally applied with field of view of micrometers or 10s of micrometers. The techniques can be combined through correlative metrology due to the possibility of multiple electron measurement techniques being housed in a single laboratory system.…”
Section: Laboratory-based Techniquesmentioning
confidence: 99%
“…c) Images from SEM and SIMS showing the elemental distribution of lithium and manganese on the crosssection of an NMC particle. Reproduced with permission [39]. Copyright 2018, Springer Nature.…”
mentioning
confidence: 99%
“…Yamagishi et al investigated and showed the Li distribution in NCA LPS ASSB using the same approach but with operando ToF-SIMS. 58,59 For coating identification, surface spectra of coated and uncoated NCM particles could be measured and the signal intensities of the coating layer mass fragments can be compared. If the sample surface is covered with contaminations, sputter cleaning must be performed in advance, ideally with an argon cluster gun to enable a gentle cleaning process and to avoid ablation of the coating layer.…”
Section: Acs Appliedmentioning
confidence: 99%